2011
DOI: 10.1007/s13595-011-0105-z
|View full text |Cite
|
Sign up to set email alerts
|

Leaf morphological and genetic differentiation between Quercus robur L. and its closest relative, the drought-tolerant Quercus pedunculiflora K. Koch

Abstract: To cite this version:Alexandru Curtu, Sofletea, Alin Toader, Mihai Enescu. Leaf morphological and genetic differentiation between Quercus robur L. and its closest relative, the drought-tolerant Quercus pedunculiflora

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…As result of interspecifi c gene fl ow and incomplete lineage sorting, genetic differentiation at nuclear (Mariette et al 2002, Muir & Schlötterer 2005, Craft & Ashley 2006, Curtu et al 2011b, Vidalis et al 2013) and cpDNA markers (Whittemore & Schaal 1991, Petit et al 2002 is very low between closely related hybridizing oak species. For example, analysis of eight genomic microsatellites in seven mixed stands of Q. robur and Q. petraea revealed that only 1.5 % of the genetic differentiation was distributed between species (Mariette et al 2002).…”
Section: Evidence For Divergent Selectionmentioning
confidence: 99%
“…As result of interspecifi c gene fl ow and incomplete lineage sorting, genetic differentiation at nuclear (Mariette et al 2002, Muir & Schlötterer 2005, Craft & Ashley 2006, Curtu et al 2011b, Vidalis et al 2013) and cpDNA markers (Whittemore & Schaal 1991, Petit et al 2002 is very low between closely related hybridizing oak species. For example, analysis of eight genomic microsatellites in seven mixed stands of Q. robur and Q. petraea revealed that only 1.5 % of the genetic differentiation was distributed between species (Mariette et al 2002).…”
Section: Evidence For Divergent Selectionmentioning
confidence: 99%
“…North American oaks also synthesize terpenoid molecules, such as isoprene, while some clades of European oaks produce other terpenoids, for example, monoterpenes [ 21 , 22 , 23 ]. Therefore typically soft, non- photosynthesizing tissues (such as young roots, germinating seedlings, buds, flowers or fruits) or young, developing leaves are preferred for genomic DNA isolation from these species as they contain higher amounts of DNA and lower amounts of potential inhibitory metabolites than mature leaves [ 24 , 25 , 26 , 27 ]. However, these tissues are often available only briefly during the lifecycle of many long-lived woody species, unless they are maintained under controlled conditions or in vitro, in tissue, or protoplast cultures, which require time consuming and costly preparation, maintenance, and additional resources that often unavailable at education centered, applied learning institutions [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The season-long availability of mature leaves is often greater for many woody species of interest for genomic studies in temperate regions, or year-round in some species, such as live oaks ( Quercus virginiana ) in the Southern United States or the Japanese evergreen oaks ( Quercus acuta ) in Eastern Asia. However, their direct applications are limited due to the difficulties in isolating high quality and quantity DNA from the metabolite rich tissue [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaf descriptors are the most commonly used morphological variables for distinguishing between oak species. Leaf morphology of European white oak species has been studied extensively using both traditional morphometric methods (Kremer et al 2002;Gugerli et al 2007;Curtu et al 2011b) and geometric morphometric methods ). In the last 2 decades, different types of genetic markers have been used for species delimitations (Petit and Excoffier 2009).…”
Section: Introductionmentioning
confidence: 99%